2001
DOI: 10.1007/pl00000849
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate and nitrite transport in bacteria

Abstract: The topological arrangements of nitrate and nitrite reductases in bacteria necessitate the synthesis of transporter proteins that carry the nitrogen oxyanions across the cytoplasmic membrane. For assimilation of nitrate (and nitrite) there are two types of uptake system known: ABC transporters that are driven by ATP hydrolysis, and secondary transporters reliant on a proton motive force. Proteins homologous to the latter type of transporter are also involved in nitrate and nitrite transport in dissimilatory pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(138 citation statements)
references
References 43 publications
7
121
1
3
Order By: Relevance
“…The genomic structure of R. solanacearum's nitrate assimilation network is unique to a subset of Betaproteobacteria. Genomic analysis suggests R. solanacearum has two assimilatory nitrate uptake systems, encoded by nasFED and narK3 (26,27). The nasFED operon, predicted to encode the typical assimilatory nitrate transporter, is atypically distant from the metabolic operon, suggesting a relatively recent genomic rearrangement (27).…”
Section: Resultsmentioning
confidence: 99%
“…The genomic structure of R. solanacearum's nitrate assimilation network is unique to a subset of Betaproteobacteria. Genomic analysis suggests R. solanacearum has two assimilatory nitrate uptake systems, encoded by nasFED and narK3 (26,27). The nasFED operon, predicted to encode the typical assimilatory nitrate transporter, is atypically distant from the metabolic operon, suggesting a relatively recent genomic rearrangement (27).…”
Section: Resultsmentioning
confidence: 99%
“…The NarG-rich communities also showed a high number of nitrate/nitrite antiporters (NarK), which import nitrate into the cytoplasm and export nitrite from it ( Fig. 5) (40). This result showed that different sponge communities use analogous pathways for denitrification, although it is not clear why these preferences for NarG or NapA exist.…”
Section: Functional Annotation Reveals Shared Genomic Signatures In Smentioning
confidence: 98%
“…For further reduction, nitrite will now be actively transported to the periplasm, where it is reduced to NO by Nir. Both processes, export to the periplasm and nitrite reduction rate, are controlled via activity of a NarK-type transporter protein (Moir and Wood, 2001;Zumft, 1997) and Nir activity, respectively. A stable equilibrium between both reactions (i.e., the rates k 3 and k 5 ) could theoretically explain the constant isotope offset: if the fraction of exported vs. reduced nitrite remains constant, the same holds for the fraction of substrate versus the original concentration resulting in a constant value for ln(f ).…”
Section: Fractionation During Nitrite Processing?mentioning
confidence: 99%